PENERAPAN MODEL INKUIRI TERBIMBING BERBASIS METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIII - Faujiati, Siti; Lumbu, Albert; triwiyono, triwiyono (Papua Journal of Physics Education, 2024)
Research has been carried out with the aim to determine the existence of an increase and the difference in learning outcomes of students with learning using the experimental method guided inquiry method. This type of research is quantitative research with quasi experimental research methods, with a non-equivalent control group design form. This research was conducted at SMP Negeri 2 Jayapura in the academic year 2018/2019. The population is 200 students of class VIII. The research sample used was class VIIID as the experimental class and class VIIIE as the control class with a sample of 60 students. The learning result analysis technique used is n-gain analysis and t-test while the questionnaire uses percentage. The results of the research and processing of test data obtained n-gain learning outcomes of 0.69 which are in the medium category. Asymp. Sig. (2-tailed) value of 0,000 <0,05, then Ho is rejected and Ha is accepted, which means there is a difference in the increase in student learning outcomes that is significant. The results of the processed response data in the form of student questionnaires to the guided inquiry learning model are known that 60% of students respond adequately and 30% of students respond well. Then it can be concluded that the application of a guided inquiry learning model is sufficient and effective to improve student learning outcomes in vibration and wave material.